Treatment-related mortality in children with acute lymphoblastic leukemia in a low-middle income country - Rahat-Ul-Ain; Mahwish Faizan; Wasila Shamim (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the proportion of treatment-related mortality (TRM) among mortalities of Pediatric Acute Lymphoblastic Leukemia (ALL), to identify probable causes and risk factors. Methods: An observational; retrospective, cohort study. Pediatric patients of ALL who expired during treatment were enrolled. Death due to relapse and deaths before treatment were excluded. Retrospective data was collected from ward record and analyzed in SPSS 16. Results: Total 247 patients of ALL expired while 144 patients were enrolled as per inclusion criteria. The proportion of TRM was 58.3%. Median age was 5 years. Male-to-female ratio was 1.3:1. Commonest cause of TRM was sepsis (n=126, 87.5%), followed by hemorrhagic complications (n=11, 7.6%), drug toxicity (n=4, 2.8%), tumor lysis syndrome (n=2, 1.4%) and thromboembolism (n=1, 0.7%). Significant factors associated with TRM were weight-for-age, immunophenotype, reason for admission and absolute neutrophil count. Conclusion: Treatment-related mortality though potentially avoidable is still a major cause of death among pediatric patients of ALL in low-middle income countries. Sepsis is the most common cause and infection prevention and control is vital in improving survival. Best supportive care must be made available for the patients on induction chemotherapy, with concomitant malnutrition, high-risk immunophenotype and profound neutropenia. Continuous...